'From Russia with Fun!': Tetris, Korobeiniki and the ludic Soviet. Issue 1 (1st October 2015) - Plank-Blasko, Dana
2014 marks the 30th anniversary of Alexei Pajitnov's puzzle game Tetris. The simple, addictive interface created an instant sensation upon its 1989 US release. The anniversary thus represents a convenient occasion to reexamine this 8-bit classic, now a vaunted member of the ludic canon.Reflecting anxieties about what lay behind the Iron Curtain, video games of the 1980s tended to represent Soviets as vodka-addled adversaries. Tetris was the first to present Soviet elements in a more positive light, illuminating changing US attitudes at the end of the Cold War. Once western game developers obtained marketing licenses, they emphasized the game's origins with red packaging, images of the Kremlin, and the hammer and sickle. Russian musical selections added geographical specificity and commercial interest. The Soviet elements drew gamers' attention, and the game's addictive nature created habitual – even compulsive – players. Tetris afforded gamers a metaphorical connection to previously forbidden, exotic territory. The construction of a new ludic Soviet sets Tetris apart from other games of this era. By exploring Tetris's historical narrative in a context of more hostile representations, we craft a new understanding of the game's role in constructing a new cultural discourse situated at an important moment in US history.